Trilobatin as an HIV‐1 entry inhibitor targeting the HIV‐1 Gp41 envelope. Issue 13 (6th June 2018) - Yin, Shuwen; Zhang, Xuanxuan; Lai, Fangyuan; Liang, Taizhen; Wen, Jiayong; Lin, Wanying; Qiu, Jiayin; Liu, Shuwen; Li, Lin
Abstract : HIV‐1 transmembrane protein gp41 plays a crucial role by forming a stable six‐helix bundle during HIV entry. Due to highly conserved sequence of gp41, the development of an effective and safe small‐molecule compound targeting gp41 is a good choice. Currently, natural polyanionic ingredients with anti‐HIV activities have aroused concern. Here, we first discovered that a glycosylated dihydrochalcone, trilobatin, exhibited broad anti‐HIV‐1 activity and low cytotoxicity in vitro . Site‐directed mutagenesis analysis suggested that the hydrophobic residue (I564) located in gp41 pocket‐forming site is pivotal for anti‐HIV activity of trilobatin. Furthermore, trilobatin displayed synergistic anti‐HIV activities combined with other antiretroviral agents. Trilobatin has a good potential to be developed as a small‐molecule HIV‐1 entry inhibitor for clinical combination therapy. Abstract :